The Influence Of Interest In Learning And Historical Awareness On History Learning Outcomes At SMK Negeri 4 Jakarta - Hakim, Nusa Peninda; Fakhruddin, Muhammad; Abrar, Abrar (UNIVERSITAS PAKUAN, 2020)
This study aims to examine the effect of interest in learning and historical awareness on learning outcomes at SMK Negeri 4 Jakarta. This research was conducted on grade XI students at SMK Negeri 4 Jakarta from April to May 2024. The research method used is ex-post facto research. The research results are as follows. 1) Learning interest has a significant positive effect on the learning outcomes of grade XI students in Indonesian History at SMK Negeri 4 Jakarta. 2) Historical awareness has a significant positive effect on the learning outcomes of 11th grade students in Indonesian History at SMK Negeri 4 Jakarta. 3) Learning interest and historical awareness have a significant positive effect on the learning outcomes of grade XI students in Indonesian History at SMK Negeri 4 Jakarta. Based on the results of this study, it can be concluded that learning interest and historical awareness have an effect on the history learning outcomes of grade XI students of SMK Negeri 4 Jakarta.